Determining of Treatment Tactic and Planning of Atypical Removal of Asymptomatic and Without Any Pathological Changes Impacted Mandibular Third Molars - Vares Y.; Kyyak S. (Львівський клінічний вісник)
Introduction. Management of the asymptomatic and without any pathological changes impacted mandibular third molars should be based on a detailed assessment of all advantages and risks. It is very important to make a correct diagnosis based on the clinical and radiologic data and to prognose the eruption or pathological changes appearance. While the number of asymptomatic and without any pathological changes impacted mandibular third molars is approximately 80.0 %, the question of prophylactic removal is actual. Simultaneously, a considerable prevalence of mandibular third molar impaction in the clinical practice of dental surgeon causes careless attitude to the stage of atypical removal planning. This provokes unpredictable prolongation of operative time, postoperative period, intra- and postoperative complications, which arise in 30.0–40.0 % of the cases. The aim of our study was to create an algorithm for determining of the treatment strategy for patients with asymptomatic and without any pathological changes impacted mandibular third molars and create scheme of their atypical removal in accordance to the clinical case. Material and research methods. With the aim of correct management of asymptomatic and without any pathological changes impacted mandibular third molars a number of criterion were collected and classified. In order to perform a correct planning, prediction of atypical removal and analysis of potential postoperative complications we created a computer program ″Xray analyzer″. Results of the investigation and their discussion. 21 criteria written in the table (table 1) give us a possibility to find out a proper treatment tactic, namely removal of lower third molar. For planning the operation we used the computer program ″Хray analyzer″ which helped us to shorten the time of operation and avoid the intra- and postoperative complications. Conclusion. Created algorithm of clinical and radiologic examination of the patients helps in indicated clinical case to set indications for correct management of asymptomatic and without any pathological changes impacted mandibular third molar. Detailed diagnostic and operation planning with the help of computer program considerably simplify operation process and reduce the intra- and postoperative complications.